New Age Movement in Holistic Christian Education and Mission Perspectives: An Integrative Approach - Danik Astuti Lumintang; Stevri Penti Novri Indra Lumintang (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The New Age movement represents a significant social and religious phenomenon that has displayed and continues to create a transformative influence on several aspects of society, including religious beliefs and practices, as well as the field of Christian religious education. The influence of the New Age Movement on Christianity has been observed among various Christian individuals and communities, including those in Indonesia. This study aimed to find a model of Christian education and a missionary approach to reach out to new Christian community agers. This study uses integrative research methods. The results of the study found an integrative model that includes nine stages in reaching new agers: changing evangelical thoughts that are negative towards new agers, loving new agers with sincerity, stopping thinking negatively about new agers, being friends for new agers, knowing new agers, understanding what new agers understand, inviting new agers, sharing good news, and disciplining them.